From Policy to Practice: Addressing Private Sector Needs in Developing Countries - Indra Aditya; Gun Gun Gumilar (Spirit Publik: Jurnal Administrasi Publik, 2025)
Employment policies play a crucial role in promoting economic growth and social stability in developing countries. With the global unemployment rate reaching 5.8% by 2022 (ILO, 2023) and the private sector contributing around 90% of the total employment in developing countries, an in-depth understanding of the relationship between employment policies and private sector needs is crucial. This narrative review analyzes the comprehensive literature from various sources to identify the key areas of policy reform. The results reveal several key challenges: regulatory burdens that limit formal business growth by 24% (Bruhn & McKenzie, 2014), significant skills gaps (Hanushek & Woessmann, 2008), limited access to finance (Beck & Demirguc-Kunt, 2006), and premature deindustrialization (Rodrik, 2016). The research findings suggest that the effectiveness of an employment policy depends on its ability to integrate the various dimensions of the challenge while considering the local context. This study emphasizes the importance of a holistic and adaptive policy approach and identifies the need for further studies on the impact of digitalization and informal sector dynamics in developing countries.